Helmintos en Pelecanus thagus y Spheniscus humboldti de la costa de Lima, Perú - Angulo Tisoc, José (2018)
In June 2012, as a result of a marine phenomenon that resulted in the death of birds of several species of seabirds, endoparasites were studied in two pelicans (Pelecanus thagus) and two penguins (Spheniscus humboldti) found dead on the beach in the district of Chorrillos, Lima (Peru). The helminths were obtained from the digestive tract in both species using the Travassos protocols. The nematodes Contracaecum rudolphii and Syngamus trachea, the cestode Tetrabothrius sp, the trematode Galactosomum puffini and the acanthocephalan Corynosoma sp were identified in Pelecanus thagus. In Spheniscus humboldti, the trematode Cardiocephaloides physalis and the nematodes Contracaecum pelagicum and Cyathostoma phenisci were identified. Syngamus trachea, Galactosomum puffini, Corynosoma sp and Contracaecum pelagicum are considered new reports in Pelecanus thagus in Peru. In addition, Spheniscus humboldti can be considered new host of Cardiocephaloides physalis and Cyathostoma phenisci.